(untitled) (Politeja, 2023)
TAIWAN’S CLIMATE DIPLOMACY: ON THE WAY TO CLIMATE NEUTRALITY The aim of this paper is to present the Taiwan’s policies and actions relating to climate change. Despite the exclusion from the United Nations Framework Convention on Climate Change (UNFCCC), Taiwan has voluntarily ratified global climate conventions and has implemented a number of legislative, technical and organizational measures to reduce the emissions of greenhouse gasses and reach net zero carbon emissions by 2050. Tackling both climate change and minimizing its effects is a priority for Taiwan. In order to achieve the sustainable development goals Taiwan treats renewable energy as a critical solution in combating climate change and ensuring energy security by adding diversity to an overall electricity mix.